Konsep humanisme religius sebagai bentuk toleransi keluarga multiagama di Malang - Hikmiyah, Hawa Hidayatul (AS-SAKINAH, 2025)
Religious humanism which is theocentric, has the principle that religion can affect human life, sees individuals and society based on moral values, as is commonly found in religion. In religious humanism, religion can provide a solution. Religious humanism can also be interpreted as Gus Dur's humanism, because it is based on Islamic universalism which is believed to be able to solve human problems. Considering that Indonesia is a country with a pluralistic society, it is feared that religious intolerance will occur. By using the concept of religious humanism, it is hoped that it can become a foothold in maintaining religious harmony. By using a descriptive qualitative approach, this study focuses on the paradigm of religious humanism as a form of tolerance for harmony in multi-religious families. This study reveals that religious humanism can be used as a new paradigm for the author. Because this humanism is a universal humanism, this idea can encompass all aspects of every religion in Indonesia. Even though they have different religions, if someone holds tightly to the same goal in the family, namely humanity, then division will not occur in the family. In line with that, this study will see how Gus Dur's concept of religious humanism as a form of tolerance in multi-religious families in Malang.